P632Beat-to-beat variability in preload unmasks reduced repolarization reserve in anesthetized dogs with chronic atrio-ventricular block: a role for mechano-electrical feedback. (15th July 2014) - Oosterhoff, P; Stams, TRG; Heijdel, A; Dunnink, A; Beekman, HDM; Van Der Nagel, R; Van Rijen, HVM; Van Der Heyden, MAG; Vos, MA
Abstract: Pronounced beat-to-beat variability in cardiac repolarization duration (BVR) is associated with increased arrhythmic risk in patients, animal models and isolated cardiomyocytes. However, the mechanisms linking an enhanced BVR to arrhythmogenicity is unknown and may differ between single cells and the intact heart, since cellular coupling is known to attenuate repolarization variability and suppress early afterdepolarizations. We hypothesized that in dogs with chronic AV-block (CAVB) and reduced repolarization strength, beat-to-beat variability in preload, only present in the intact heart, is required to increase BVR. Methods: Endocardial left ventricular monophasic action potential duration (LVMAPD80) was recorded in acute (AAVB, n=6) and CAVB dogs (n=7), before and after a challenge with the IKr blocker dofetilide. We used atrial and ventricular stimulation to provide either a constant or an alternating preload pattern, which was verified by PV-loop determined mechanical parameters. The effect of the stretch activated channel blocker streptomycin on baseline BVR and arrhythmic response to dofetilide was evaluated in a second CAVB group (n=9). Short-term variability of LVMAPD was used to quantify BVR. Arrhythmic outcome was quantified by combining the number of ectopic beats, episodes of TdP and defibrillations into a single arrhythmia score (AS). Results: Pro-arrhythmic remodeling (>3weeks AV-block) increased BVR during alternating preload, (0.45±0.14 AAVB vs 2.2±1.1 ms CAVB, p<0.01), while no change in BVR was seen at constant preload (0.35±0.12 AAVB vs 0.32±0.14 ms CAVB, NS). At AAVB, reduction of repolarization reserve by dofetilide did not induce TdP (AS 1[1-2], median[IQR]), but was pro-arrhythmic in CAVB (AS 27[9-62], p<0.05 vs AAVB). Variation of preload did not alter arrhythmic outcome at CAVB (AS 16[7-37] constant vs 47[2-57] alternating, NS), but was present in BVR determined prior to arrhythmias (2.5±1.4 constant vs 5.9±4.5 ms alternating, p=0.08). In the second group, the increase in BVR at baseline by alternating preload (0.3±0.03 vs 1.0±0.8 ms, p<0.01) was almost abolished by streptomycin (0.5±0.2 ms alternating, p<0.05 vs baseline alternating, NS vs baseline constant). Furthermore, arrhythmia score after dofetilide was reduced after streptomycin pre-treatment (AS 4[2-13], p=0.05). Conclusions: In the anesthetized CAVB dog BVR is a marker of pro-arrhythmic remodeling and critically reduced repolarization reserve, and originates from altered response to changes in preload. There is involvement of stretch activated channels both in the mechanisms of BVR and of drug-induced arrhythmia.